2008
DOI: 10.1016/j.yhbeh.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and Kennedy disease/spinal bulbar muscular atrophy

Abstract: Kennedy Disease/Spinal Bulbar Muscular Atrophy (KD/SBMA) is a progressive neurodegenerative disease caused by genetic polyglutamine expansion of the androgen receptor. We have recently found that overexpression of wildtype androgen receptor in skeletal muscle of transgenic mice results in a KD/SBMA phenotype. This surprising result challenges the orthodox view that KD/SBMA requires expression of polyglutamine expanded androgen receptor within motoneurons. Theories relating to the etiology of this disease drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 76 publications
0
21
0
1
Order By: Relevance
“…motor impairment and wasting) has proven difficult (Monks et al 2007). As we have argued elsewhere (Monks et al 2008), this difficulty might be explained by a quantitative difference resulting in a threshold for pathology being met. We might, therefore, predict that testosterone-exposed L78 and L141 mice would exhibit similar alterations in cellular processes, but that they would be more pronounced in L141 mice, culminating in systemic dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…motor impairment and wasting) has proven difficult (Monks et al 2007). As we have argued elsewhere (Monks et al 2008), this difficulty might be explained by a quantitative difference resulting in a threshold for pathology being met. We might, therefore, predict that testosterone-exposed L78 and L141 mice would exhibit similar alterations in cellular processes, but that they would be more pronounced in L141 mice, culminating in systemic dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…As an example, the view that BSMA requires poly-G-expanded AR for disease expression has been recently challenged by the finding that over-expression of wild-type AG in the skeletal muscle of transgenic mice may also manifest as BSMA [88]. Also poly-Q-expanded AR acting in muscle fibers can trigger a BSMA phenotype and secondarily may cause motor neuron dysfunction, challenging the role of AR in muscle [2].…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Many studies have revealed various types of AR gene mutations that contribute to diseases including spinobulbar muscular atrophy (SBMA) (26), androgen insensitivity syndrome (AIS) (27), and prostate cancer (28, 29). Several reports have revealed that mutant ARs obtained from both AIS and prostate cancer patients may exhibit abnormal intracellular localization and lower capacity for ligand-dependent translocation when compared with wild-type AR.…”
Section: Introductionmentioning
confidence: 99%